The influence of Carnival, grotesco criollo and other forms of popular performance on Beckett´s theatre in Argentina - Nudler, Alicia Clara (2025)
Fil: Nudler, Alicia Clara. Universidad Nacional de Río Negro. Río Negro; Argentina.